Design through research: Handpicking tools case study as facilitator to collaborative product development / Azmir Mamat Nawi and Wan Zaiyana Mohd Yusof - Mamat Nawi, Azmir; Mohd Yusof, Wan Zaiyana (Universiti Teknologi MARA, Kedah, 2011)
Collaboration between research and design is believed by many design theorists to offer new originality, insight and specialist expertise for product design. In practice, however, there exists a discrepancy between this ideal and a reality of unreconcilable cultural and methodological differences. This project has proven that the collaboration between research and design fuels creativity. This study documents and discusses such a collaboration as an example of practice with implications for educators, designers and students. It identifies a new role with the appropriate knowledge and experience to act as bridges within companies, facilitating the adoption of design methodologies appropriate to changing priorities in the design industries.